Land use conflict : a case study for Tapah area, Siburan sub-district, Sarawak - Jaynsen Patrick, Sibat (Universiti Malaysia Sarawak (UNIMAS), 2004)
The goal of the study was to identify the impacts of land use conflicts on the water quality of Sungai Tapah sub-catchment, Siburan Sub-district, Kuching, Sarawak. Data were collected by visiting various Government departments, private agencies, informal interviews, literature search, and field visits to the study area. At present, 15 water catchment areas have been gazetted under the provision of the Water Ordinance, 1994. The Natural Resources and Environment Board (NREB) have approved another 17 water catchment areas for gazettement, which is also devising a policy for introducing guidelines on permitted activities within water catchment areas. Although no agriculture is allowed in water catchment areas, encroachment by small-scale farming and shifting cultivation occurs in the study area, thus creating land use conflicts. Many concur that shifting cultivation is one of the main causes of siltation and river sedimentation in the State, particularly when appropriate fallow periods are not practiced. Results from the water quality analysis indicated a higher level of suspended solids and turbidity during the first sampling (high tide and after rainfall), as compared to the second sampling conducted during low tide and no rainfall prior to the sampling. This is indicative of surface runoff and the lack of groundcover to prevent it from reaching the waterways. In general, the water samples taken from Sungai Tapah are acceptable. However, this is not the case for the discharge water from the water treatment plant (sample WS3). The level of suspended solids and turbidity are considered Class V of the Interim National Water Quality Standards for Malaysia (INWQSM). Therefore, the protection of our water supply should be of highest priority. Currently, shifting cultivation is not under any form of regulation, thus has the potential to cause adverse environmental impacts due to the vastness of these areas in the State. An integrated approach, whereby social, economic and environmental dimensions are taken into consideration, is used to formulate effective strategies and management frameworks for water resources management in order to tackle this problem.